1991
DOI: 10.1007/bf03007620
|View full text |Cite
|
Sign up to set email alerts
|

Time-cycled inverse ratio ventilation does not improve gas exchange during anaesthesia

Abstract: Time-cycled inverse ratio ventilation does not improve gas exchange during anaesthesiaInverse ratio ventilation (IRV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Prolonged inspiratory time is beneficial only when a significant amount of recruitable lung units exist. This could be the reason why previous studies failed to show or showed marginal effects of IRV in subjects under general anaesthesia . However, pneumoperitoneum in the Trendelenburg position causes a cephalad shift of the diaphragm and closure of small airways, considerably increasing the number of recruitable lung units .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Prolonged inspiratory time is beneficial only when a significant amount of recruitable lung units exist. This could be the reason why previous studies failed to show or showed marginal effects of IRV in subjects under general anaesthesia . However, pneumoperitoneum in the Trendelenburg position causes a cephalad shift of the diaphragm and closure of small airways, considerably increasing the number of recruitable lung units .…”
Section: Discussionmentioning
confidence: 98%
“…There are previous reports of applying IRV during general anaesthesia . Tweed and Lee investigated the effect of IRV during orthopaedic surgery under general anaesthesia and found that increasing Pmean by time‐cycled IRV has no beneficial effect on pulmonary mechanics or gas exchange . They also applied pressure‐controlled IRV in patients undergoing lower abdominal gynaecologic surgery in the Trendelenburg position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been reports of using IRV during general anaesthesia. Whilst IRV had no beneficial effects when patients were placed in the supine position , arterial oxygenation increased slightly when patients were placed in the Trendelenburg position . Another study reported that IRV reduced intra‐operative A‐aDO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Inverse‐ratio ventilation is a prolonged inspiratory time compared with expiratory time and is known to be effective for increasing oxygenation and reducing peak airway pressures in adults with respiratory distress syndrome and respiratory failure . Previous studies evaluating the effect of IRV during general anaesthesia revealed no muscle‐sparing or only a marginal improvement in gas exchange ; however, there have been no studies investigating the effectiveness of IRV in subjects undergoing OLV for lung surgery. The aim of our study was to evaluate whether a prolonged inspiratory time improves gas exchange and respiratory mechanics in patients undergoing lung surgery with OLV compared with conventional ventilatory settings.…”
mentioning
confidence: 99%